RESEARCH OF THE PROPERTIES OF PROTEINS FROM WHEAT BRAN IN BAKERY PRODUCTS - Qodiraliyeva, H.G.; Amanov, B.N.; Iskandarova, Sh. M.; Rahimova, M.Z.; Nurmatov , J.J. (Innovative Development in Educational Activities, 2024)
In a wide range of food products with controlled composition and nutritional properties, for the production of protein products, it is advisable to use raw materials that actually exist in the country - wheat bran. In terms of water-binding capacity, bran protein flour is close to full-fat soy flour and surpasses all other protein products in this indicator. Bran products have a high fat-binding ability to form an emulsion type. Along with the ability to change the surface tension at the oil-water interface, bran protein products had a similar property in relation to phases.